REKONSTRUKSI PERAN DAN HAK PEREMPUAN DALAM ORGANISASI MASYARAKAT ISLAM - Suhendra, Ahmad (Musawa Jurnal Studi Gender dan Islam, 2012)
Islam as a religion of rah}mat for all of nature, without knowing the sex and gender. However, the role and rights of women is often times overlooked in public relations. Islamic community organizations as well as institutions have not provided a significant change in gender issues. Thus, this article will try to reconstruct the gender issues on women and the Islamic community organizations, especially related to the role and rights of women in the organization.